THE EFFECT OF POE LEARNING MODEL (PREDICT, OBSERVE, EXPLAIN) ON STUDENTS’ SCIENCE PROCESS SKILLS - Hidayat, Rahmat; Samputri, Salma; Yunus, Sitti Rahma (Universitas Negeri Makassar, 2024)
This study aims to determine: 1) the level of students’ science process skills (SPS) who taught using POE learning model in experimental class and conventional learning model in control class at SMPN 2 Sungguminasa, 2) the improvement of SPS after applying POE learning model in experimental class and conventional learning model in control class. 3) the effect of POE learning model on the SPS. This type of research is Quasi-Experimental with Nonequivalent Control Group Design. The results of analysis showed that: 1) the level of SPS of VIII grade students that taught using the POE learning model is in the high category with an average score of 16.80 and the control class is in the medium category with an average score of 13.53 2) The improvement of SPS of VIII grade students after applying the POE learning model is in the medium category with an average N-Gain score of 0.42. And in the control class is in the medium category with an average N-Gain score of 0.33 3) There is an effect of POE learning model on the KPS of VIII grade students of SMPN 2 Sungguminasa.